2019
DOI: 10.29271/jcpsp.2019.02.105
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Magnetic Resonance Imaging (DWI) Parameters in Benign and Malignant Ovarian Tumors with Solid and Cystic Components

Abstract: from January to December 2017. Forty-four patients with malignant ovarian tumours confirmed by clinicopathology were selected as a malignant group. At the same time, 44 cases of benign ovarian tumours confirmed by clinic pathology were selected as a benign

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This finding is supported by the study of Zhuang and colleagues. 25 , who reported that the solid ADC in the benign group was significantly higher than the malignant group. The explanation for this may be that there was a higher rate of proliferation of malignant cells and a relatively small cell distance with a high molecular activity of water.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is supported by the study of Zhuang and colleagues. 25 , who reported that the solid ADC in the benign group was significantly higher than the malignant group. The explanation for this may be that there was a higher rate of proliferation of malignant cells and a relatively small cell distance with a high molecular activity of water.…”
Section: Discussionmentioning
confidence: 98%
“…The present study results resembled with Elsammak et al, findings, who divided 42 lesions into 24 cases of benign lesions and 18 cases of malignant lesion group [12] and found that endometrial hyperplasia was the most common benign lesions whereas endometrial carcinoma was malignant lesions. Y. Zhuang et al found that in malignant lesions, endometrial carcinoma was the most prevalent endometrial lesions [13]. Another study conducted by Wang et al reported that 40 malignant lesions out of total 42 lesions were endometrial carcinoma and 7 out of 14 benign lesions were endometrial polyps.…”
Section: Discussionmentioning
confidence: 98%
“…It is also important to compare [ 68 Ga]Ga-PSMA-11 PET/CT with MRI including diffusionweighted imaging (DWI) and dynamic contrast-enhanced imaging (DCE), which now seems to very promising in differentiation of benign and malignant ovarian tumours [10,30].…”
Section: Discussionmentioning
confidence: 99%